Modal Nafkah Rumah Tangga Petani Cabai Jawa (Piper retrofractum Vahl) di Lahan Kering Desa Gudangharjo Kecamatan Paranggupito Kabupaten Wonogiri - Lingga Sukma Handari; Widiyanto Widiyanto; Emi Widiyanti (Universitas Sebelas Maret, 2025)
The livelihood activities of farmers’ households face various challenges that put farmers in a vulnerable condition and encourage them to utilize their own resources. These resources are referred to as livelihood assets. The livelihood assets of farmers’ households are managed to sustain life and meet daily needs. This research aims to analyze the daily life of Java long pepper farmers’ households in managing their livelihood assets (human, natural, financial, physical, and social). This study uses a descriptive qualitative method. The informants were determined using purposive sampling and snowball sampling, resulting in 13 informants, including the Village Head of Gudangharjo, 10 Java long pepper farmers, a collector, a community leader, and a representative from Sido Muncul. Data collection techniques included in-depth interviews, observation, documentation, and interactive analysis using Miles and Huberman’s approach. Livelihood assets owned by Java long pepper farmers households in Gudangharjo Village include (a) Natural capital, consisting of land ownership and ownership level of Java long pepper plants and coconut trees; (b) Human capital, consisting of formal education level, skills, and labor allocation; (c) Physical capital, consisting of motorcycle ownership and livestock; (d) Financial capital, consisting of savings in the form of livestock and stored rice, access to loans, and remittances from children; (e) Social capital, consisting of the utilization of networks with collectors that guarantee farmers’ income, neighborly or fraternal relationships that ensure labor in agricultural enterprise and social support, and participation in farmer group organizations that ensure farmers receive subsidized fertilizer.